2022
DOI: 10.1111/jhn.12997
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of plasma vitamin C concentrations in individuals requiring home parenteral nutrition

Abstract: Background Ascorbic acid (VitC) is an essential coenzyme to maintain health, but there are minimal data on the adequacy of VitC supply in patients requiring home parenteral nutrition (HPN). Methods A prospective pilot study was carried out measuring plasma VitC, serum vitamins A, D and E, and the minerals zinc, copper, selenium and magnesium in 28 adult HPN‐dependent (≥6 months) patients. Results Fifty‐seven percent of patients had insufficient VitC status. There was a strong, positive correlation between HPN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The results were variable, with not all studies showing an association between dose and serum levels. All three studies that evaluated serum vitamin C levels showed an association between parenteral dose when subgroups were compared; however, in contrast to the other two studies, 21,65 Stevens 18 found a higher dose in those with a serum level <26.1 μmol compared to those with in‐range levels. This may reflect the study design with multiple samples reported per participant in the study by Stevens 18 , and vitamin C dose may have been increased in response to a previous low serum level, which remained low on repeated testing.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…The results were variable, with not all studies showing an association between dose and serum levels. All three studies that evaluated serum vitamin C levels showed an association between parenteral dose when subgroups were compared; however, in contrast to the other two studies, 21,65 Stevens 18 found a higher dose in those with a serum level <26.1 μmol compared to those with in‐range levels. This may reflect the study design with multiple samples reported per participant in the study by Stevens 18 , and vitamin C dose may have been increased in response to a previous low serum level, which remained low on repeated testing.…”
Section: Resultsmentioning
confidence: 84%
“…Five of the nine studies assessing serum 25‐hydroxy‐vitamin D levels reported dose administered, with four of these also reporting other sources. When HPN intake was compared, this was not associated with a difference in serum level 18,21 . Tee et al23 compared those receiving HPN vitamin D only ( n = 162) with those ( n = 13) receiving three monthly intramuscular injections (median (CI) with serum levels 52.0 (54.8, 65.4) compared to 70.0 (55.2–109.6) nmol/L ( p = 0.023); however, the duration of supplementation was not reported.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations